Development and characterization of orthotopic patient-derived xenograft models of peritoneal metastatic mucinous appendiceal adenocarcinoma - I. Ito; V.K. Pattalachinti; A.M.G. Yousef; S. Chowdhury; M.M. Fanaeian; E. Haque; B.B. Gunes; M. Yousef; E.R. Salle; M.A. Zeineddine; S. Ji; R. Li; et al. (ESMO Gastrointestinal Oncology)
Background: Appendiceal adenocarcinomas (AAs) are a rare and heterogeneous group of tumors for which few preclinical models exist. The lack of preclinical models of AA has hindered drug development and is a major factor in why AA remains without a single Food and Drug Administration-approved systemic treatment. Materials and methods: Tumors from 16 patients with appendiceal neoplasms (15 AAs and 1 high-grade appendiceal neoplasm) were implanted into the flank and the peritoneal cavity of immunodeficient mice leading to the successful establishment of three AAPDX models. Histological, immunohistochemical, genetic, and transcriptomic comparisons of patient and patient-derived xenograft (PDX) tumors were carried out. Results: Higher tumor grade, peritoneal implantation, and RAS/RAF mutation were associated with successful tumor engraftment. Comparison of histological, immunohistochemical, and molecular analyses including both RNA and DNA sequencing revealed that the PDX models recreate many of the features of metastatic AAs, but also displayed several differences between paired PDX and human tumors, highlighting the intratumoral heterogeneity of AAs within each patient. Notably tumors from two patients with primarily low-grade mucinous adenocarcinoma converted to high-grade histology in PDX. Transcriptomic comparison of patient and PDX tumors identified increased Myc and E2F signaling, suggesting that activation of Myc may be a driver of the dedifferentiation of AAs. The established PDX models were able to undergo serial passaging and expansion and exhibited stable histological features during this process, allowing for drug testing. Conclusions: These molecularly profiled, orthotopic PDX models of metastatic AAs represent a unique resource for future exploration to identify novel therapies for this orphan disease.